2021
DOI: 10.1007/s00404-021-06070-2
|View full text |Cite
|
Sign up to set email alerts
|

Poly (adenosine diphosphate [ADP]–ribose) polymerase (PARP) inhibitors as maintenance therapy in women with newly diagnosed ovarian cancer: a systematic review and meta-analysis

Abstract: Purpose To investigate the efficacy and safety of poly (adenosine diphosphate [ADP]–ribose) polymerase (PARP) inhibitors (including their different types) as maintenance therapy in women with newly diagnosed ovarian cancer, and to explore whether this therapy produces a survival benefit in a subgroup population with specific clinical characteristics. Methods We searched MEDLINE, EMBASE, the Cochrane Library, Web of Science and relevant clinical research re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The model used in this study computed ICERs of olaparib plus bevacizumab versus bevacizumab alone were $249,579, $258,859, and $270,736 per QALY for patients with BRCA mutations, patients with HRD, and patients with HRD without BRCA mutations AOC, respectively. While not cost-effective, the combined olaparib plus bevacizumab regimen was associated with more favorable health benefits in patients with BRCA mutations and HRD-positive AOC, in line with several prior reports [ 37 38 39 40 ]. In two recent retrospective analyses of 33 and 42 patients in France and China harboring BRCA mutations or HRD-positive AOC, respectively, designed to assess prognostic outcomes associated with PARP inhibitor treatment, the median PFS and OS of patients with BRCA mutations were 20.9 vs. 37.7 months (p=0.210) and 151.2 vs. 122.5 months (p=0.520), while HRD status was an independent predictor of PFS (HR=0.67; 95% CI=0.49–0.92; p=0.010) [ 37 38 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The model used in this study computed ICERs of olaparib plus bevacizumab versus bevacizumab alone were $249,579, $258,859, and $270,736 per QALY for patients with BRCA mutations, patients with HRD, and patients with HRD without BRCA mutations AOC, respectively. While not cost-effective, the combined olaparib plus bevacizumab regimen was associated with more favorable health benefits in patients with BRCA mutations and HRD-positive AOC, in line with several prior reports [ 37 38 39 40 ]. In two recent retrospective analyses of 33 and 42 patients in France and China harboring BRCA mutations or HRD-positive AOC, respectively, designed to assess prognostic outcomes associated with PARP inhibitor treatment, the median PFS and OS of patients with BRCA mutations were 20.9 vs. 37.7 months (p=0.210) and 151.2 vs. 122.5 months (p=0.520), while HRD status was an independent predictor of PFS (HR=0.67; 95% CI=0.49–0.92; p=0.010) [ 37 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…In two recent retrospective analyses of 33 and 42 patients in France and China harboring BRCA mutations or HRD-positive AOC, respectively, designed to assess prognostic outcomes associated with PARP inhibitor treatment, the median PFS and OS of patients with BRCA mutations were 20.9 vs. 37.7 months (p=0.210) and 151.2 vs. 122.5 months (p=0.520), while HRD status was an independent predictor of PFS (HR=0.67; 95% CI=0.49–0.92; p=0.010) [ 37 38 ]. Two other meta-analyses including 5,005 and 3,070 patients with OC revealed significant PARP inhibitor-related improvements in the PFS of patients with BRCA mutations OC (HR=0.29; 95% CI=0.24–0.34 and 0.34; 0.28–0.41) and HRD-positive OC (HR=0.40; 95% CI=0.32–0.48 and 0.39; 0.29–0.53) [ 39 40 ]. As these new combination treatment regimens are associated with high costs, alternative treatments should be considered as appropriate for patients with AOC based on their molecular status, with the early detection of these prognostic biomarkers being vital to achieving optimal patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the BRCA mutation status and HRD status of AOC patients were taken into consideration in the present study in an effort to provide better evidence-based guidance for both healthcare providers and payers. The calculated ICERs of olaparib plus bevacizumab versus bevacizumab monotherapy were $79,434/QALY, $141,636/QALY, and $ 200,595/QALY for BRCA mutations, HRD-positive, and HRD-positive without BRCA mutations AOC patients, respectively, suggesting that this combined treatment regimen is only cost-effective for the former two patient subgroups in line with prior evidence [ 40 43 ]. Two recent retrospective reports focused on 33 and 42 AOC patients in France and China with BRCA mutations or HRD-positive disease, respectively, found that PARP inhibitor treatment was associated with, the median PFS and OS in BRCA mutation-positive patients of 20.9 vs. 37.7 months (P = 0.21) and 151.2 vs. 122.5 months (P = 0.52), whereas HRD status was identified as an independent predictor of PFS (HR, 0.67; 95%CI, 0.49 to 0.92; P = 0.01)[ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 70%
“…In two other meta-analyses enrolling 5,005 and 3,070 OC patients. PARP inhibitor treatment was associated with significantly improved PFS in both BRCA mutations (HR, 0.29; 95%CI, 0.24 to 0.34 and 0.34; 0.28 to 0.41) and HRD-positive (0.40; 0.32 to 0.48 and 0.39; 0.29 to 0.53) OC patients [ 42 , 43 ]. Given the high costs associated with these novel therapeutic regimens, alternative treatment options for AOC patients should be taken into consideration in light of their molecular status, and the evaluation of these prognostic biomarkers at an early time point remains essential to ensuring that these patients experience optimal.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant clinical benefit of PARP inhibitors in progression-free survival (PFS) compared to placebo in maintenance therapy with homologous recombination deficiency (HRD). Therefore, maintenance therapy with PARP inhibitors can significantly prolong PFS in patients with newly diagnosed ovarian cancer ( 183 ).…”
Section: Therapiesmentioning
confidence: 99%